A Contemplative Tool: An Exposé of the Performance of Self. (April 2017) - Klatt, Maryanna D.
Contemplative education courses and academic programs emerging in universities across the United States and internationally have a unique opportunity to help students gain both self-awareness and an awareness of how the self is situated in a larger context. Research utilizing meditation in higher education shows promise in strengthening stress resilience, interpersonal skills, and the cognitive capabilities of attentional control and the processing of information. Pragmatic, reflective pedagogical assignments that successfully cultivate personal and social awareness need to be shared. This article details an educative experience for students in a higher education contemplative education course. The course utilizes guided mindfulness meditation and reflective writing to help students reflect upon their "performance of self" to increase awareness and potentially help sculpt their personal and professional lives. This pedagogy demonstrates an innovative and creative application of the theory of contemplative practice in action.